Fausto Felipe Rodríguez, uno de los iniciadores de la Cirugía Maxilofacial cubana - Morales Navarro, Denia; Cruañas Sospedra, Carlos Manuel; Miranda Tarragó, Josefa Dolores (Revista Cubana de Estomatología, 2019)
.